Lecturers’ Moonlighting and Job Effectiveness in Public Universities in North-Central Nigeria - Walbe, Setka G.; Gyang, Theresa Stephen (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The study examined the extent of public University lecturers’ moonlighting on their job effectiveness in North-central Nigeria. University lecturers lack conducive economic work environment needed for their job performance. In this regard, their disposition, interest in the job, dedication and commitment which are important in academic staff job performance are lacking and Universities’ goals are not met. The research design adopted for this study was the descriptive survey method. The population of this study consists of all the seven thousand seven hundred and forty seven (7747) academic staff members and two hundred and fifty three thousand eight hundred and seventy two (253872) students working and studying in the thirteen public Universities and the Federal Capital Territory in North-central Nigeria. The sample of 501 lecturers and 2363 students from six public Universities was used. This was based on the Yamene (1967) formula for sampling. Data was collected using the ‘Moonlighting and Academic Staff Job Effectiveness Questionnaire (MASJEQ) for lecturers and Academic Staff Effectiveness Questionnaire (ASEQ) for students. Mean, Standard Deviation were used to answer the research questions while Pearson Correlation was used to test the hypothesis at 0.05 level of significance. The findings revealed that the moonlighting activities done by academic staff in public Universities in North-central Nigeria are private part-time teaching, farming and attending small gardens, petty trading, and salon activities. The study also revealed the causes of the academic staff moonlighting behavior among them are unconducive work environment in terms of insufficient salary, lack of incentives, extended family, and high demand of lecturers in the region due to the establishment of new Universities and other higher institutions. The result further revealed that moonlighting for lecturers affects lecturers’ job effectiveness in teaching, research and community service activities in public Universities in North-central Nigeria. The result showed that there is significant relationship between lecturers’ moonlighting activities and their job effectiveness in public Universities in North-central Nigeria. Thus, in order for academics staff to be effective in their job duties, administrators should encourage conducive work environment for lecturers. Keywords: Lecturer  moonlighting, job effectiveness and public universities